The Effectiveness of Bitter Melon Juice Consumption (Momordica Charantia L.) in Reducing Blood Sugar Levels in Diabetes Mellitus Patients - Dameria Gultom; Septika Siahaan; Masryna Siagian (Jurnal Ners, 2026)
Diabetes mellitus is a metabolic disorder characterized by chronic hyperglycemia and represents a rapidly growing public health problem worldwide and in Indonesia. Management of this disease can be undertaken through pharmacological and nonpharmacological approaches, one of which is the utilization of Momordica charantia L. (bitter melon) containing charantin, polypeptide-p, and lectin as hypoglycemic compounds. This study aimed to analyze the effectiveness of bitter melon juice consumption in reducing blood glucose levels among patients with diabetes mellitus in the working area of UPT. Puskesmas Soposurung in 2026. This was a quantitative study employing a quasi-experimental design with a pre-test and post-test non-equivalent control group design. The population comprised 118 patients with type 2 diabetes mellitus, from which 60 respondents were recruited through quota sampling and allocated into an experimental group (n=30) and a control group (n=30). The intervention consisted of 200 mL of bitter melon juice administered daily for 10 days. Random blood glucose was measured using a glucometer. Data were analyzed using the Wilcoxon Signed-Rank Test and the Mann-Whitney U Test. The Wilcoxon test revealed significant differences in blood glucose levels before and after measurement in the control group (p=0.013) and in the experimental group (p<0.001). The Mann-Whitney test showed a significant difference in effectiveness between the two groups (p<0.001). Bitter melon juice consumption was proven effective in reducing blood glucose levels among patients with type 2 diabetes